Exploratory study of sea buckthorn enhancing QiangGuYin efficacy by inhibiting CKIP-1 and Notum activating the Wnt/β-catenin signaling pathway and analysis of active ingredients by molecular docking - Yuan, Yi-Feng; Wang, Shen; Zhou, Hang; Tang, Bin-Bin; Liu, Yang; Huang, Hai; He, Cai-Jian; Chen, Tian-Peng; Fang, Mou-Hao; Liang, Bo-Cheng; Mao, Ying-De-Long; Qie, Feng-Qin; et al. (Frontiers in Pharmacology, 2022)
Background: Sea buckthorn (SBT) is a traditional Chinese medicine (TCM), rich in calcium, phosphorus, and vitamins, which can potentially prevent and treat osteoporosis. However, no research has been conducted to confirm these hypotheses. QiangGuYin (QGY) is a TCM compound used to treat osteoporosis. There is a need to investigate whether SBT enhances QGY efficacy. Objectives: The aim of this study was to explore whether SBT enhances QGY efficacy by inhibiting CKIP-1 and Notum expression through the Wnt/β-catenin pathway. The study also aimed to explore the active components of SBT. Methods: Experimental animals were divided into control, model, QGY, SBT, SBT + Eucommia ulmoides (EU), and SBT + QGY groups. After treatment, bone morphometric parameters, such as estrogen, PINP, and S-CTX levels, and Notum, CKIP-1, and β-catenin expression were examined. Screening of SBT active components was conducted by molecular docking to obtain small molecules that bind Notum and CKIP-1. Results: The results showed that all the drug groups could elevate the estrogen, PINP, and S-CTX levels, improve femoral bone morphometric parameters, inhibit Notum and CKIP-1 expression, and promote β-catenin expression. The effect of SBT + EU and SBT + QGY was superior to the others. Molecular docking identified that SBT contains seven small molecules (folic acid, rhein, quercetin, kaempferol, mandenol, isorhamnetin, and ent-epicatechin) with potential effects on CKIP-1 and Notum. Conclusion: SBT improves bone morphometric performance in PMOP rats by inhibiting CKIP-1 and Notum expression, increasing estrogen levels, and activating the Wnt/β-catenin signaling pathway. Furthermore, SBT enhances the properties of QGY. Folic acid, rhein, quercetin, kaempferol, mandenol, isorhamnetin, and ent-epicatechin are the most likely active ingredients of SBT. These results provide insight into the pharmacological mechanisms of SBT in treating osteoporosis.